Raidal Forearm Island Flap in the Management of Severe Adduction Contracture of Thumb - G. S. Kalra; S. K. Bhatnagar; R. Chandra; S. D. Pandey (Indian Journal of Plastic Surgery)
The use of radial forearm flap as a distally based island flap for severe adduction contracture of thumb is being presented. The advantages and vascular basis of this flap has been discussed.